Water regime effect on growth and antioxident content of pursalne - Su, Ging Sam; Uddin, Md Kamal (LAP LAMBERT Academic Publishing, 2018)
Purslane (Portulaca oleracea) is naturally found in turfgrass areas as well as field crops. Drought stress is considered as one of the crop performance limiting factors and a threat for successful crop production. With respect to the importance of purslane as a medicinal and valuable plant and because of low information regarding its physiological and chemical reactions under water stress, doing this project is necessary. Field capacity condition had produced purslane with longest internode length (76mm), highest leaf relative water content (79.85%), highest total phenolic content (3.06 mg GAE/g), and highest ash content (17.5%). Continuous saturated condition produced purslane with highest plant height (429.0mm). Continuous flooded condition produced purslane with highest total flavonoid content (1.35 mg QE/g), nitrogen (3.14%) and crude protein content (19.62%). It may be recommended as a water saving technology for the water scarce areas for purslane production. The antioxidant content and nutritional value of purslane are important for human consumption. The book is useful for postgraduate students, lecturers and researchers.